"It's no good but at least I've always got it round my neck": A postphenomenological analysis of reassurance in assistive technology use by older people. (January 2022) - Lynch, Jennifer; Hughes, Gemma; Papoutsi, Chrysanthi; Wherton, Joseph; A'Court, Christine
Abstract: The provision of reassurance is seen as a goal and benefit of the use of assistive technology (AT) in supporting people to manage their health and care needs at a distance. Conceptually, reassurance in health and care settings remains under-theorised with the benefits of experiencing reassurance through technology use assumed rather than understood. UK health and social care service goals of managing safety and risk have largely been equated with providing reassurance to users of AT and their carers. What has not been explored is how reassurance is experienced variably by users of different types of technology-enabled care. We present data from 3 case studies of different technologies in use in health and social care provision, analysed through a postphenomenology and sociomaterial lens. Our findings point to reassurance as an important facet of AT provision but the intended functions and uses of technological devices alone did not account for people's experiences of reassurance. Participant narratives referred variously to the comfort of being monitored, having their illness/wellness verified by the device, feeling reassured by the promise of help if needed, and imbuing the device with symbolic meaning (when the user associated the device with meanings and functions other than its technical capabilities). The different ways in which reassurance was experienced provides a useful way of understanding the potential tensions with AT policy goals as well as the positive meaning attributed to devices in some cases. This study reaffirms the importance of AT implementation being anchored in what matters to the user. Highlights: Reassurance is a goal of assistive technology implementation for the care of older people. Postphenomenology can account for variations in people's experiences of technology. People feel reassured through multistable human-technology relations. A technology's materiality can generate symbolic meaning for the user. Technology implementation must incorporate users' needs changing over time.